PERSEPSI PENYAKIT DAN KEPATUHAN KONTROL PASIEN HIPERTENSI USIA DEWASA - Ode Irman; Anggia Riske Wijayanti; Yohanes Paulus Pati Rangga (Journal of Nursing Care and Biomolecular, 2023)
Hypertension in adults increases every year and is responsible for complications and death. Preventing complications and death from hypertension requires adherence to treatment controls. Illness perception can affect adherence to treatment controls. The purpose of this study was to explain the correlation between illness perception and control adherence in adult hypertensive patients. This type of research is correlational analytic with a cross-sectional approach. The study involved 42 patients who were taken by purposive sampling and carried out at the Nita Public Health Center, Sikka Regency, East Nusa Tenggara in March 2023. Data collection used the brief illness perception questionnaire (B-IPQ) and the Morisky medication adherence scale (MMAS-8). Data analysis used the contingency coefficient test. The results showed that there was a correlation between illness perception and control compliance in adult hypertensive patients (p 0.000). The higher the illness perception, the more it is considered a threat to health and increases control adherence. Therefore, it is very important to increase the illness perception to achieve high control compliance in adult hypertensive patients. It is expected that nurses in providing care to hypertensive patients, must consider these aspects.   Keywords: Adherence, Adults, Hypertension, Illness Perception